2019
DOI: 10.1016/j.conbuildmat.2019.05.106
|View full text |Cite
|
Sign up to set email alerts
|

ASR expansions at the level of a single glass-cement paste interface: experimental results and proposal of a reaction-expansion mechanism

Abstract: h i g h l i g h t sNew experimental setup for studying ASR expansions at aggregate-cement interfaces. ASR interfacial expansion curves of SL glass-cement interfaces are obtained. ASR products at the glass-cement interfaces are studied via SEM/EDS analyses. A reaction-expansion mechanism for ASR in SL glass concrete is proposed. The role of calcium: different swelling pressures of low-and high-Ca ASR products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Other experimental works found that the Ca/Si ratio of the ASR gel in the glass cracks is much lower than that at the glass paste interface (Rajabipour et al 2010;Shim 2019;Liaudat et al 2019). This is because of calcium ions originating from the paste neighboring the glass particles.…”
Section: Introductionmentioning
confidence: 91%
“…Other experimental works found that the Ca/Si ratio of the ASR gel in the glass cracks is much lower than that at the glass paste interface (Rajabipour et al 2010;Shim 2019;Liaudat et al 2019). This is because of calcium ions originating from the paste neighboring the glass particles.…”
Section: Introductionmentioning
confidence: 91%
“…Some of the more recent methods and tests [29][30][31][32][33] were further reviewed in a study by Figuera et al [3], in which they stated that ASR and its treatment are influenced by more factors that are still unfound in literature. Their study concludes that while massive efforts have been devoted to manipulating ASR, the ability to understand it entirely remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…When the glass is used in concrete with particle sizes greater than 0.5 mm, the development of the AAR is observed. However, when ground in dimensions smaller than 100 µm, it can present a pozzolanic behavior and reduce the expansion potential of the ASR [7].…”
Section: Introductionmentioning
confidence: 99%